Complement Component 3 Is Associated with Metabolic Comorbidities in Older HIV-Positive Adults - Bryant, Alex K. (AIDS Res Hum Retroviruses, 2016)
Our objective was to evaluate the association of plasma inflammatory biomarkers with MetS in an older population of treated HIV-infected (HIV(+)) as compared to age-matched HIV-negative (HIV(−)) adults. This was done in a retrospective observational study. Plasma concentrations of complement component 3 (C3), cystatin C, fibroblast growth factor 1, interleukin 6, oxidized LDL, soluble RAGE, soluble CD163, soluble CD14, and osteopontin were measured in 79 HIV(+) participants on combination antiretroviral treatment (cART) with a suppressed HIV viral load and 47 HIV(−) participants with a median age of 59 (range 50 to 79). Outcomes were individual MetS components (hypertension, type II diabetes, dyslipidemia, and obesity) and MetS. Covariates were screened for inclusion in multivariable models. Odds ratios are reported per 50 mg/dl increase in C3. In the HIV(+) group, higher C3 levels were associated with MetS (OR 3.19, p = 0.004), obesity (OR 2.02, p = 0.01), type II diabetes (OR 1.93, p = 0.02), and at a trend level with dyslipidemia (OR 1.87, p = 0.07) and hypertension (OR 1.66, p = 0.09). C3 levels were significantly higher in HIV(+) participants with MetS compared to those without MetS (p = 0.002). C3 was higher among HIV(+) patients with three or four MetS components as compared to those with one or two (p = 0.04) and those with none (p = 0.002). No associations were found between C3 and the outcomes for HIV(−) participants. C3 is strongly associated with both MetS and MetS components in an older HIV(+) sample on cART compared to HIV(−) controls. C3 warrants further investigation as a marker of cardiometabolic risk among persons aging with HIV.